Optimization of Catfish (Pangasius sp) Bone Bio-calcium Production with Different Concentrations of Citric Acid and Stirring Time Using the Response Surface Method (RSM) Approach - Wijayanti, Ph.D, Ima; Agustini, Tri Winarni; Swastawati, Fronthea; Anggo, Apri Dwi; Afifah, Diana Nur (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
Calcium is an important macro-mineral that is really needed by the body.Calcium from fish bones can be an alternative source of calcium for thosewho are allergic to milk lactose which is usually used as calcium source. Theweakness of fish bone calcium is that it still has a fishy odor, which reducesthe hedonic value of products fortified with fish bone calcium. This researchaims to determine the optimization of concentration and stirring time in citricacid to produce bio-calcium from catfish (Pangasius sp) bones with the bestcalcium content and hedonic characteristics using Response SurfaceMethodology (RSM). The citric acid concentration tested was a minimum of0.25% and a maximum of 1% with stirring times of 30, 60 and 90 min. Dataprocessing was carried out with the help of Design Expert 11 software. Therecommended model is the quadratic model. The recommended optimizationresults for the bio-calcium production solution are a citric acid concentrationof 0.25% and a soaking time of 30 min. Verification was carried out accordingto the optimization solution and gave yield results of 88.9%, particle size of51.07 µm, calcium content 24.05; with a color hedonic value of 4.115, aroma4.059 and overall 4.090 out of a maximum value of 5. XRD pattern showed nodifference between fishbone powder and bio-calcium with degree crystallinity57 and 56.2%, respectively. FTIR spectra showed that both fishbone powder andbio-calcium powder contained hydroxyapatite, however citric acid slightly removedprotein due to absence of amide 1 peaks in bio-calcium powder. Citric acid at0.25% for 30 min helped to increase the yield and reduced some organiccompound to obtain bio-calcium powder. The proper concentration of citric acidand stirring time yielded catfish bone bio-calcium with higher calcium contentand hedonic value.